2019
DOI: 10.3390/molecules24173061
|View full text |Cite
|
Sign up to set email alerts
|

Computational Approaches for Drug Discovery

Abstract: Computational approaches represent valuable and essential tools in each step of the drug discovery and development trajectory [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…Molecular docking is one of the most popular methods in the field of computer-aided drug design (CADD) for the identification of new drug leads [ 21 ]. CADD is currently being used to rapidly annotate and analyze large drug libraries, thereby saving an immense amount of energy, time, and costs [ 22 , 23 ]. The current study examined a total of 169 compounds, as shown in Table S1 .…”
Section: Discussionmentioning
confidence: 99%
“…Molecular docking is one of the most popular methods in the field of computer-aided drug design (CADD) for the identification of new drug leads [ 21 ]. CADD is currently being used to rapidly annotate and analyze large drug libraries, thereby saving an immense amount of energy, time, and costs [ 22 , 23 ]. The current study examined a total of 169 compounds, as shown in Table S1 .…”
Section: Discussionmentioning
confidence: 99%
“…Computational drug design methods have become very reliable and widely used in drug discovery processes nowadays [ 20 , 21 , 22 ]. Molecular docking and molecular dynamics simulations help scientists greatly in the fast-track discovery of new drug candidates [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several computational approaches help researchers in the discovery of new drug candidates. An example of these in silico techniques is structure-based virtual screening and molecular docking studies [ 9 ]. On the other hand, bioinformatics can be used to detect the main key amino acids at nearly the same normal conditions, and, hence, confirming the docking results and druggability will be also easier to handle.…”
Section: Introductionmentioning
confidence: 99%